Bond characterization of monolithic and layered glass panels and ultrasonic tests to control glued surfaces. (1st November 2019) - Campione, Giuseppe; Orlando, Francesco; Fileccia, Giuseppe; Pauletta, Margherita
Highlights: Shear strength of monolithic and PVB laminated glass elements connected though acrylic glue. Ultrasonic tests were utilized to control the efficiency of glued surfaces of glass panels. Experimental shear test of glass elements. Shear stress-slippage curves from bond test. Ultrasonic tests detect gluing defects generated artificially. Abstract: An experimental investigation is presented regarding the compressive and shear strength of monolithic and PVB laminated glass elements connected by acrylic glue. Ultrasonic tests were also used to control the efficiency of glued surfaces of glass panels. Twenty-four triplets composed of three float glass elements glued with acrylic adhesive were prepared to perform bond tests. Of these twelve triplets were made with monolithic glass elements with a nominal thickness of 20 mm, while twelve were made with layered glass elements 20 mm thick. Three single elements of monolithic glass and three of layered glass were tested for compressive strength. Ultrasonic tests were performed on a sample made by gluing two layered glass panels 200 × 300 × 20 mm in thickness in which defects in glued surfaces were generated artificially. Experimental stress-strain curves in compression for glass elements and shear stress-slippage curves from bond tests were also derived with crack patterns at rupture.